A multi-channel integrated auditory function test system - Xiao, Shijie; Zheng, Yihang; Lin, Guanting; Liu, Jinxuan; Xiong, Wei; Song, Lei; Chen, Fangyi (Neuroscience, 2025)
•Developed a multi-channel ABR testing system for mice, increasing auditory function assessment throughput by 3-4 folds.•Integrated DPOAE, CM and CAP measurements-especially in the high-frequency range, enabling systematic evaluation of the murine auditory system.•Performance is comparable to the industry-standard Tucker-Davis Technologies (TDT) system. The auditory brainstem response (ABR) remains the gold standard for evaluating hearing function in both animal models and humans. Features of ABR, including threshold, wave I amplitude and latency are critical for diagnosing and investigating the mechanisms of hearing loss. Critically, the rapid proliferation of genetically engineered mouse models in hearing research has created an imperative demand for high-throughput ABR testing capabilities. Currently, the Tucker-Davis Technologies (TDT) system serves as the standard, and nearly exclusive, platform for animal ABR assessment. However, the design of single-animal testing system, with low sampling rates, serves as limitation to certain applications such as large-scale screening and studies of high frequency distortion product otoacoustic emission (DPOAE) and cochlear microphonic (CM). We developed a four-channel ABR system enabling simultaneous testing of four subjects, coupled with a custom acoustic chamber providing > 50 dB noise attenuation across mouse hearing frequencies. The system’s enhanced acoustic and electrical performance obtains high-frequency (>32 kHz) DPOAE and CM recordings beyond the capabilities of the TDT System3 and RZ6. In mouse ABR assessments, it consistently replicates TDT-measured thresholds, wave I latency, and amplitude while tripling test throughput. This comprehensive platform meets modern high-volume ABR demands, delivering superior efficiency and expanded functional assessment for scalable, high-fidelity auditory phenotyping in next-generation research.